Commodification and transfiguration: Socially mediated identity in technology and theology - Cole-Turner, Ronald (HTS teologiese studies, 2019)
Social media platforms like Facebook and Twitter allow users to create an online identity with preferences, photos including ‘selfies’ and links to other users. These platforms allow users to present and edit their identities or profiles in accordance with their subjective desires and aspirations as well as in response to feedback from others. Defining individual identity online presents new challenges for many individuals. This article explores those challenges and engages the culture and the practices of online identity formation critically. Identity formation online raises profound theological questions, which are explored in relation to Christian theology and its understanding of personhood as defined in relationship. This view originates in the earliest Christian theology as an attempt to understand the Christian God as three identities that are mutually defined by their relationship to each other. The article asks how the experience of identity formation online in social media can challenge and inform a Christian view of the human relationship with the divine.